Teori Behavior dalam Meningkatkan Motivasi Hafalan Surat Pendek Al-Quran - Marlina Marlina (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
This research reveals the processes, outcomes and factors that influence from the implementation of behavioral theory with reward techniques in improving the motivation of memorizing the Quran short letter to class B in Kondergarten Al-Quran Darussalam. The method used in this research is descriptive method by using qualitative approach. Data collection techniques are done through observation, principal direct interview with classroom teacher, and documentation, using data reduction analysis, data presentation and final conclusion (verivication). The results obtained in this study indicate that the giving of rewards by classroom teachers to their students in improving the motivation of memorizing the Quran short letter to the child in TKA Darussalam Pameungpeuk, has effective results and very influential in improving the motivation of rote children. Reward provided by the supervisor/ teacher is reward verbal and reward non-verbal. Penelitian ini mengungkapkantentang proses, hasil dan faktor-faktor yang mempengaruhi dari pelaksanaan teori behavior dengan teknik reward dalam meningkatkan motivasi hafalan surat pendek Al-Quran pada kelas B di Taman Kanak-Kanak Al-Quran (TKA) Darussalam. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan menggunakan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara langsung kepala sekolah dengan guru kelas, dan dokumentasi, dengan menggunakan analisis reduksi data, penyajian data dan penyimpulan akhir (verifikasi).Hasil yang didapat dalam penelitian ini menunjukkan bahwa pemberian reward yang dilakukan oleh guru kelas kepada siswanya dalam meningkatkan motivasi hafalan surat pendek Al-Quran pada anak di TKA Darussalam Pameungpeuk, memiliki hasil yang efektif dan sangat berpengaruh dalam meningkatkan motivasi hafalan anak-anak. Reward yang diberikan oleh pembimbing/guru yaitu, reward verbal reward non-verbal.